THU0213 Adalimumab in Combination with Methotrexate for The Treatment of Juvenile Idiopathic Arthritis Associated Uveitis: The Sycamore Trial. (15th July 2016) - Ramanan, A.V.; Dick, A.D.; Jones, A.P.; McKay, A.; Williamson, P.R.; Compeyrot-Lacassagne, S.; Hardwick, B.; Hickey, H.; Hughes, D.; Woo, P.; Benton, D.; Edelsten, C.; et al.
Abstract : Background: Uveitis associated with Juvenile Idiopathic Arthritis (JIA) is a major cause of morbidity with potentially sight-threatening complications. Despite current screening and (pre-biologic) therapeutic options, 10–15% of children develop bilateral visual impairment. Tumour necrosis factor alpha plays a pathogenic role in JIA-uveitis. No controlled trials have determined the impact of biologic therapy in JIA-associated uveitis. Objectives: To compare the clinical effectiveness of adalimumab in combination with methotrexate (MTX) versus MTX alone, with regard to controlling disease activity in refractory uveitis associated with JIA. Methods: Patients aged 2 to 18 years with active JIA-associated uveitis, despite stable methotrexate (MTX) treatment for at least 12 weeks, were randomly assigned to adalimumab or placebo in a ratio of 2:1. All patients were treated up to a maximum period of 18 months, with follow up of 2 years from randomisation. All patients received a stable dose of MTX and in addition either adalimumab (20 mg for patients weighing <30 kg or 40 mg for patients weighing ≥30 kg, subcutaneous injection every 2 weeks) or placebo. Primary endpoint was "time to treatment failure" defined by the "Standardisation of the Uveitis Nomenclature" criteria. Ten secondary efficacy endpoints were assessed including quality of life variables and arthritis disease activity measures. Adverse events from both arms were collected. Post-hoc analyses investigated "time to treatment response" and the proportion of responders, failures or those who had no change at three and six months. Statistical analysis of the primary outcome used the log rank test to compare treatment groups with a hazard ratio and 95% confidence interval also being reported. Results: The trial was stopped early for reasons of efficacy after 90 patients had been randomised and the interim analysis met the pre-specified statistical stopping guidelines. The final analysis of the primary outcome showed a positive treatment effect in favour of adalimumab: hazard ratio (HR) 0.25 (95% CI 0.12–0.49); p<0.0001. Adverse events were experienced by 88.3% (53/60, 694 events) of patients in the adalimumab group and 90% (27/30, 144 events) of patients in the placebo group. Events were consistent with the known adalimumab profile. Post-hoc analyses showed significant differences showing favourable response to Adalimumab with respect to both the time to treatment response HR 3.15 (95% CI 1.42 to 7.00); p<0.0027 and the proportion of responders at both three and six months (p=0.0014 for each timepoint). Conclusions: This trial, the largest of its kind to be conducted in JIA-associated uveitis, provides evidence of efficacy of adalimumab treatment used in addition to methotrexate in this population. The safety profile of adalimumab was consistent with that previously reported for adalimumab. Acknowledgement: This project was funded by the National Institute for Health Research Health Technology Assessment Programme (project 09/51/01) and Arthritis Research UK (grant reference 19612) Disclosure of Interest: None declared